Analisis Konsentrasi Debu Jatuh (Dustfall) Di Pemukiman Sekitar Pabrik Pengolahan Crude Palm Oil (CPO) - Tridani, Pipi Domita Anggun; Hafidawati, Hafidawati; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Crude Palm Oil (CPO) processing plant PT. Z Pelalawan Regency is one of the palm oil processing factories that uses palm kernel shells and fiber as an energy source. Palm oil processing is certainly inseparable from the problem of air pollution, especially in the environment, namely pollutant gases and dust. This study aims to analyze the concentration of dustfall based on the measurement distance from the pollutant source. Sampling of dustfall using a Dustfall Collector based on SNI 13-4703-1998. Variation of dust sampling distance falls 0 m, 300 m, 1230 m from the pollutant source. The results showed that the highest concentration of dustfall was at a distance of 0 m from the pollutant source with an average value of 24.46 g/m2/month and the lowest at a distance of 1230 m with an average value of 5.13 g/m2/month.Keywords: Shell, Fiber, Distance, Concentration of Dustfall, Palm Oil Mill